2023
DOI: 10.3390/molecules28041623
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Ferroptosis and Cuproptosis in Curcumin against Hepatocellular Carcinoma

Abstract: Background: Among cancer-related deaths, hepatocellular carcinoma (HCC) ranks fourth, and traditional Chinese medicine (TCM) treatment is an important complementary alternative therapy for HCC. Curcumin is a natural ingredient extracted from Curcuma longa with anti-HCC activity, while the therapeutic mechanisms of curcumin remain unclear, especially on ferroptosis and cuproptosis. Methods: Differentially expressed genes (DEGs) of curcumin treatment in PLC, KMCH, and Huh7 cells were identified, respectively. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Multiple drugs and molecules have been shown to be effective in inhibiting osteosarcoma progression by inducing ferroptosis. Liu et al found that synthetic analogues of curcumin induced ferroptosis by increasing MDA levels, ROS levels, and intracellular iron ion levels 30 . Wen et al found that baicalin induced ferroptosis in osteosarcoma through a novel Nrf2/xCT/GPX4 regulatory axis 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Multiple drugs and molecules have been shown to be effective in inhibiting osteosarcoma progression by inducing ferroptosis. Liu et al found that synthetic analogues of curcumin induced ferroptosis by increasing MDA levels, ROS levels, and intracellular iron ion levels 30 . Wen et al found that baicalin induced ferroptosis in osteosarcoma through a novel Nrf2/xCT/GPX4 regulatory axis 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Bioinformatics analysis is widely used to explore the complex mechanisms and effective targets of drug treatment. According to the analysis of relevant data, dehydroabietic acid [ 239 ], curcumin [ 240 ], and Astragalus membranaceus [ 241 ] could exert their potential effect in treating HCC by regulating ferroptosis-related genes or pathways. It is expected that more effective targets will be identified with the development of various omics techniques and analytical methods.…”
Section: Nac Treat Liver Disease By Targeting Ferroptosismentioning
confidence: 99%
“…Furthermore, several emerging molecular mechanisms related to curcumin's treatment of HCC should be mentioned. (Liu et al, 2023). Moreover, curcumin has been shown to reduce HCC resistance to lenvatinib by modulating the EGFR signaling pathway (Miyazaki et al, 2023).…”
Section: Curcuminmentioning
confidence: 99%
“…Zhu et al suggested that curcumin inhibited HCC metastasis by modulating the TET1/Wnt/β‐catenin signaling pathway (J. Zhu, Qu, et al, 2022). Liu et al proposed that curcumin induced ferroptosis and cuproptosis in HCC cells to inhibit tumor development (Liu et al, 2023). Moreover, curcumin has been shown to reduce HCC resistance to lenvatinib by modulating the EGFR signaling pathway (Miyazaki et al, 2023).…”
Section: Mechanisms Of Polyphenolic Compounds Protect Against Hepatic...mentioning
confidence: 99%